Обгрунтування ринкової стратегії в роботі транспортно-експедиторської компаннії - Очеретна, В. В. (НТУ "ХПІ", 2014)
У статті розглянута ринкова стратегія транспортно-експедиторської компанії як об'єкту управління, розуміння її внутрішніх взаємозв'язків і механізмів функціонування. Обґрунтовується цілісна відкрита система компанії з певною внутрішньою організацією. А також розглядається рівень організації процесів, якість їх виконання, що впливають на кінцеві споживчі властивості транспортно-експедиторської послуги, які у свою чергу безпосередньо пов'язані з конкурентоспроможністю послуги.

The article market strategy of a freight forwarder company is considered as a object of management, understanding of her internal intercommunications and mechanisms of functioning. Integral open system of company is grounded with a certain internals. And the level of organization of processes is similarly examined, quality is their implementations, influencing on eventual consumer properties of a freight forwarder service, that in turn is straight related to the competitiveness of service. On the whole consumer properties of the service got on an exit and accordingly competitiveness of company depend on quality of resources and execution of processes. Companies, that today will be able to reduce perspective market niches and concentrate the activity on them, guess the changes of market demand and adapt under them the internal possibilities able one of the first to volunteer service to the market, with such descriptions for that a consumer is ready expensive to pay, in the future will occupy leading position.
Grounding of market strategy in the work of a freight forwarder company
Keywords: ринок послуг; транспортно-експедиторські послуги; конкурентоспроможність; експедитор; сукупність ресурсів; стратегічний потенціал; freight forwarder company; competitiveness; resources; transportation; service; consolidation